Pemanfaatan Periklanan sebagai Sarana Perkembangan Dakwah Islam di Era Digitalisasi - Erwan Efendi; Peby Shinta Siregar; Sutan Pardomuan Ritonga (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
In the current Era of Digitalization, da'wah activities are growing along with the development of science and technology. Islamic da'wah can be disseminated through various media without reducing the meaning and purpose of Islamic da'wah. One of the media that is used as a means of da'wah is advertising where this advertising spreads very quickly in the Digital Age as we experience it today. Dakwah is an appeal or invitation to people to carry out activities based on Amar Ma'ruf Nahi Munkar. This inviting activity can be done in various ways and can use various media, one of which is through advertising media. With the development of technology, especially in the field of communication and advertising, it is very reliable as a means of spreading Islamic da'wah. Technological developments in the current era of digitalization not only lead to negative things but also have positive sides, especially as a means of spreading Islamic da'wah. Keywords: advertising marketing , development of technology, digitalization